Impact of E-Learning on College of Education Lecturers’ Knowledge of Quantitative Data Analysis in SPSS - Tolulope Adeyemi Adeniran; Samuel Adenubi Onasanya (Indonesian Journal of Educational Research and Technology, 2024)
E-learning is becoming the courseware in this global digital era transforming how learning takes place. Regardless of distance and time, e-learning is becoming unstoppable with its synchronous and asynchronous mode of instructional presentation. This study investigated the impact of e-learning on lecturers’ knowledge of quantitative data analysis in SPSS at the Federal College of Education (Special) Oyo State, Nigeria. A descriptive survey research design was adopted in the study. A total number of one hundred and fifty (150) lecturers were selected through simple random sampling techniques for the study. Purposive sampling was used to select the school that was adopted for the study. Three (3) Research questions were generated and answered in this study. Data collected from the sampled population employing a questionnaire were analyzed using simple percentages and mean scores to answer the three research questions. The results of the findings revealed that e-learning is an important platform accessible and utilized by college lecturers. The findings also revealed that lecturers gained knowledge in data analysis in SPSS through an e-learning platform as it serves as a research and leisure tool which provides various opportunities to many people worldwide, particularly college of education lecturers.